Civilization without oil: condition and perspectives of manufacture and application in Ukraine ecologically pure biodiesel fuel - Semenov, V. H. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The chain of production of biodiesel fuel from rape olive is considered, analysis of physical and chemical indexes of the biodiesel fuel and their influence on operating charecteristics of diesel engines operation is carried out.